STUDI KEBUTUHAN BUKAAN PADA BANGUNAN PERUMAHAN TYPE MENENGAH DENGAN PENDEKATAN PENCAHAYAAN - Ode Rapija GW (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2012)
The purpose of the light on the environment is to lightening every element of the buildingwhich makes the clearer visual sence. In addition, the presence of the light is hoped to comfort theperson who lives there which their activities. The building on medium size (type 45 and type 54)has the small window. Moreover, the building placed on the block only has the front window. Itcauses the building on medium size will catch less light, the room will be darker, and the lamp willbe turned on the day.The instrument of this research is a software dialux 4, 7. The advantages of using this softwaredialux 4, 7 are it will be easier and more variative in editing the geometry of the room, it will beeasier in inserting the furniture to the room which will be calculated, and the output can be conturgrid-3d.The size of the windows in the guestroom, the family room, and the diningroom of themedium building is about 4, 09- 5, 6 m2. The window in the main bedroom is about 1, 51-1, 96 m2width. The window in the children bedroom is about 1, 38-1, 64 m2 width.Keywords: window, lightening intensity.